Hilos del mismo tejido: weaving community perspectives into community-based global learning through critical micro-ethnographic testimonio - Benavides, Macario T. (Kansas State University, 2022)
As higher education institutions in the United States face pressure to develop students’ capacity to thrive in a globalized society (Niehaus et al., 2019), they have turned to international programs to address this need (LeCrom et al., 2015). In the last decade, U.S. study abroad participation has continued to rise, with short-term programs representing the most significant areas of growth (Institute of International Education, 2019a, 2019b). Short-term education abroad includes faculty-led, direct enrollment, exchange, community-based global learning (CBGL), and other international learning formats and are typically eight weeks or fewer (Niehaus et al., 2019). In this study, I examine curricular and co-curricular CBGL programs because of their potential for both positive and harmful impact (García & Longo, 2013). While global community-engaged programs may contribute to local change efforts within engaged communities, these programs often prioritize the learning outcomes related to student participation. Given this gap in reciprocal practice, programs are likely to engage in superficial change efforts and/or perpetuate global inequities stemming from colonial structures and imposed Eurocentric and U.S.-centric cultural frameworks. This study is guided by an extensive review of literature related to the field of CBGL where I identified three primary gaps related to the research questions. First, literature continues to exclude community voices from the process of developing CBGL theory, practice, and pedagogy (Kennedy et al., 2020; Larsen, 2016; Smaller & O’Sullivan, 2018; Sumka et al., 2015; Tonkin, 2011). Second, research that does surface community perspectives tends to have a narrow focus related to a specific CBGL program (Lough & Toms, 2018). Finally, CBGL scholars and educators tend to focus on positive outcomes and minimize adverse effects (Niehaus & Nyunt, 2020; Sherraden et al., 2008). Scholarship that addresses these gaps is necessary so that higher education institutions can support their students in developing the critical global competence that is promoted as a fundamental learning outcome. To address these gaps, especially within Indigenous contexts, CBGL scholars will need to actively center reciprocity at the heart of their practice, meaningfully engage Indigenous and local knowledge systems, and implicate themselves in the inequitable realities of their community partners. My study explored these gaps by examining how one non-governmental organization in the Sololá department of Guatemala describes its experiences with international volunteers from across the global north. This research can help educators, students, and community partners understand how to decolonize and indigenize short-term CBGL programs engaged with Indigenous communities and/or on Indigenous lands. Underpinning this study is my onto-epistemological foundations in social constructionism, critical theory, and indigenization; my ethical commitment to community-engaged scholarship and decolonization; and my conceptual framing of critical hope, intercultural leadership, and interculturalidad. I conducted this study through a lens of integral methodological pluralism, recognizing that converging worldviews and epistemologies remain incommensurable so long as we attempt to make meaning of them through conflicting approaches. To bridge the knowledge systems of the local community and academic tradition, I employed a blend of two relevant methodologies: testimonio and critical micro-ethnography. Through fieldwork, pláticas, researcher reflexivity, and member checking, I co-constructed a critical narrative detailing the experiences of the Guatemalan community with foreign volunteers. The findings of this study illustrated that there continues to be a gap between the established best practices related to community-engaged programs, like CBGL, and the lived experiences of the communities with which we partner. The experiences recounted by members of the Guatemalan host community reflected the issues in the field of CBGL outlined in the literature review. Similarly, the aspirations reflected in the testimonio aligned with literature related to meaningful partnerships. Through the testimonio that emerged from this study, I identified six key phases that require intentional collaboration with community partners: (1) institutional preparation, (2) partnership development, (3) program design, (4) pre-departure learning objectives, (5) program cycle debrief and evaluation, and (6) alumni engagement. Engaging in these phases in collaboration with community partners can ensure that reciprocity remains at the forefront of program design.
Keywords: Community based global learning; Global service learning; Community engagement; International education; Higher education; Reciprocity